Gramsci, historical materialism and international relations - Gill, Stephen, 1950- (Cambridge : Cambridge University Press, 1993)
The essays collected here relate the writings of Antonio Gramsci and others to the contemporary reconstruction of historical materialist theories of international relations. The contributors analyse the contradiction between globalising and territorially based social and political forces in the context of past, present, and future world orders, and view the emerging world order as undergoing a structural transformation, a 'triple crisis' involving economic, political and 'sociocultural' change. The prevailing trend of the 1980s and early 1990s toward the marketisation and commodification of social relations leads the contributors to argue that socialism needs to be redefined away from the totalising visions associated with Marxism-Leninism, towards the idea of the self-defence of society and social choice to counter the disintegrating and atomising effects of globalising and unplanned market forces.
9. Soviet socialism and passive revolution / Kees Van Der Pijl. 10. Structural issues of global governance: implications for Europe / Robert W. Cox.
Includes bibliographical references and indexes.
Keywords: Gramsci, Antonio, -- 1891-1937.; International relations; Communism and international relations; Historical materialism